Advanced pilot modeling for prediction of rotorcraft handling qualities in turbulent wind - Ji, Honglei; Lu, Linghai; White, Mark D.; Chen, Renliang (Elsevier, 2022)
Turbulent wind is known for potentially deteriorating rotorcraft performance and handling qualities when fulfilling their operation and duties. However, related research is rarely reported and could be possibly attributed to the absence of an effective analytical tool. This paper proposes a pilot model to explore the effect of turbulent wind on rotorcraft handling qualities. It consists of three components: a stabilization control component, a trajectory planning component, and a trajectory tracking component. A slalom task in the turbulent wind is used for the validation of this new pilot model. The simulation results have demonstrated that the new pilot model can not only plan and track a desired trajectory by determining a pilot's guidance strategy, but also predict handling qualities through modeling the effect of the vestibular system. The new pilot model predicts the effect of steady wind component on a pilot's maneuvering aggressiveness and yaw control performance for various ground speeds. It is also capable of predicting the handling qualities in turbulent wind due to increased turbulence intensity and reduced flight control authority.
Keywords: Pilot model; Rotorcraft; Handling qualities; Atmospheric turbulence; Flight dynamics